(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Many branches of knowledge have been studying the origin, content and importance of mobile games for a long time. The article describes the importance of mobile games in the development of physical qualities of young volleyball players.